2010
DOI: 10.3109/15368378.2010.502451
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of K562 Cells Under ELF-EMF Applied at Different Time Courses

Abstract: The time-course of ELF-EMF application to biological systems is thought to be an important parameter determining the physiological outcome. This study investigated the effect of ELF-EMF on the differentiation of K562 cells at different time courses. ELF-EMF (50 Hz, 5 mT, 1 h) was applied at two different time-courses; first at the onset of hemin induction for 1 h, and second, daily 1 h for four days. While single exposure to ELF-EMF resulted in a decrease in differentiation, ELF-EMF applied everyday for 1 h ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…The maximum possible exposure near a specific source often differs by some orders of magnitude from the average individual exposure of a person. For example, at 5 cm from a vacuum cleaner, B is of about 40 µT, but at 1 m it will be around 0.2 µT [9,10]; • alternation and duration of exposure [5][6][7][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum possible exposure near a specific source often differs by some orders of magnitude from the average individual exposure of a person. For example, at 5 cm from a vacuum cleaner, B is of about 40 µT, but at 1 m it will be around 0.2 µT [9,10]; • alternation and duration of exposure [5][6][7][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that ELF-EMF is associated with production of ROS. [16][17][18] Moreover, reduced PDYN expression in the human brain is associated with opiate dependency. 35,36 Interestingly, in the present study the continuous exposure condition of ELF-EMF was associated with the lower expression levels of the PDYN.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has been reported that ELF-EMF enhanced production of reactive oxygen species (ROS). [16][17][18] Cells maintain redox balance through production of ROS and cellular antioxidant capacity. The altered balance between generation and elimination of ROS plays a critical role in a variety of multifactorial complex traits including neurodegenerative diseases.…”
mentioning
confidence: 99%
“…Namely, application of ELF-EMF once at the onset of hemin induction may have interfered with the differentiation process and led to a decrease in differentiation as a result of increased oxidative stress and consequent MAPK signal path activation, while daily ELF-EMF application overcame this effect by an increase in HSP levels. It is debated that the time course of application and the duration may be of a nonlinear character suggesting a ''window'' effect in duration of the field application [8].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in heat-shock protein levels induced by ELF-EMF is not able to reverse the increase in the number of apoptotic cells caused by oxidative stress [7]. Based on the results of Ayse and co-workers about influence of ELF-EMF on differentiation of K562 cancer cell line, it can be concluded that ELF-EMF exposure at different timecourses results in different outcomes [8].…”
Section: Introductionmentioning
confidence: 99%